MODEL IN PROFESSIONAL NURSING EDIFICATION - K Kannan; Joseph jeganathan; Nagarajaiah (Indian Journal of Psychiatric Nursing)
Teachers and employers alike are seeking a solution to this fundamental problem of the limits of classroom education. Simulation education may hold the answer. Nursing education has long utilized simulation in some form to teach principles and skills of nursing care. Simulation activities involve controlled representations of actual clinical events. This strategy allows the learner to experience “real world” patient situations without risk. Learners are required to assess and interpret the situation, and make decisions based on information provided.